2019
DOI: 10.1021/acs.iecr.9b03916
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of NbOx on Pt/Al2O3 for Effective Catalytic Propane Oxidation

Abstract: Catalytic combustion is an effective way to eliminate volatile organic compound (VOC) pollution, such as propane. However, it is still a significant challenge to develop effective catalysts. Herein, we report NbO x -doped Pt/Al2O3 catalysts synthesized by a facile impregnation method for effective propane oxidation. New types of acidic sites are generated on the surface of Pt/Al2O3 when NbO x is added, and the acidity is gradually improved. NbO x is beneficial for the formation of Pt0 species, which obviousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 44 publications
6
24
0
Order By: Relevance
“…It is clear that the Pt/CeO 2 catalyst contains only oxidized Pt species (mainly Pt 2+ species), while a small portion of metallic Pt 0 species (with a concentration of 6.3%) can be observed in the Pt/Nb 2 O 5 catalyst. The presence of metallic Pt species in Pt/Nb 2 O 5 catalyst can be ascribed to the promoted reduction of PtO x species by the abundant medium strong and strong acid sites in Nb 2 O 5 (Figure c), namely, the strong acid sites enhance the reducibility of PtO x species, which is consistent with the previous works . Regarding the O 1s XPS spectra (Figure b), three oxygen species (e.g., O a , O b , and O c ) are observed in the Pt/CeO 2 and Pt/Nb 2 O 5 catalysts.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…It is clear that the Pt/CeO 2 catalyst contains only oxidized Pt species (mainly Pt 2+ species), while a small portion of metallic Pt 0 species (with a concentration of 6.3%) can be observed in the Pt/Nb 2 O 5 catalyst. The presence of metallic Pt species in Pt/Nb 2 O 5 catalyst can be ascribed to the promoted reduction of PtO x species by the abundant medium strong and strong acid sites in Nb 2 O 5 (Figure c), namely, the strong acid sites enhance the reducibility of PtO x species, which is consistent with the previous works . Regarding the O 1s XPS spectra (Figure b), three oxygen species (e.g., O a , O b , and O c ) are observed in the Pt/CeO 2 and Pt/Nb 2 O 5 catalysts.…”
Section: Resultssupporting
confidence: 88%
“…Figure shows the XPS spectra of Pt 4f and O 1s of the Pt/CeO 2 and Pt/Nb 2 O 5 catalysts. In Figure a, the peaks with binding energies (BEs) at 71.6 and 74.8 eV can be attributed to Pt 4f 7/2 and Pt 4f 5/2 of Pt 0 species, respectively . The peaks with BEs of 72.7 and 76.0 eV correspond to Pt 4f 7/2 and Pt 4f 5/2 of Pt 2+ species, respectively.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Developing efficient and appropriate methods to reduce propane emissions is of great significance to improve the environment. [11][12][13][14] In the past, most people used precious metals to catalyze the degradation of waste gas such as propane, for instance, Garetto et al studied the deep oxidation of propane on platinum loaded beta molecular sieves, they found that propane combustion on Pt-supported catalysts would proceed then via two simultaneous mechanisms, which the main oxidation pathway on platinum and a contributing oxidation pathway on the metal-oxide interfacial region. The subsequent oxidation mechanism increased the density of propane molecules adsorbed in the interface region.…”
Section: Introductionmentioning
confidence: 99%
“…The catalysts with 5% W loading had the highest content of Pt 0 and exhibited the best catalytic activity as well as enhanced stability. Luo's Group [25] prepared Pt-Nb/Al 2 O 3 catalysts and found that the doping of Nb could significantly increase the content of Pt 0 . The authors declared that the increase in catalytic combustion activity of propane was the result of the combined effect of Pt 0 and Pt 2+ .…”
Section: Introductionmentioning
confidence: 99%